Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s42523-019-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Faecal inoculations alter the gastrointestinal microbiome and allow dietary expansion in a wild specialist herbivore, the koala

Abstract: Background: Differences between individuals in their gastrointestinal microbiomes can lead to variation in their ability to persist on particular diets. Koalas are dietary specialists, feeding almost exclusively on Eucalyptus foliage but many individuals will not feed on particular Eucalyptus species that are adequate food for other individuals, even when facing starvation. We undertook a faecal inoculation experiment to test whether a koala's gastrointestinal (GI) microbiome influences their diet. Wild-caught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 64 publications
(88 reference statements)
0
70
0
Order By: Relevance
“…Microbial richness and diversity were also found to be lower in the microbiome of koalas feeding on manna gum, likely to be linked to a greater energy harvest from this species of Eucalyptus compared to messmate (Brice et al, 2019). Therefore it has been hypothesized that the inability of the majority of koalas to shift diets to messmate is due to a lack appropriate gut microbial assemblage for optimal digestion (Blyton et al, 2019). With the continuous threat of habitat loss and limited resources, the ability to shift diet and utilize different food sources is crucial for the survival and persistence of koalas in the wild.…”
Section: Gut Microbiome Management In Wildlife Conservationmentioning
confidence: 99%
“…Microbial richness and diversity were also found to be lower in the microbiome of koalas feeding on manna gum, likely to be linked to a greater energy harvest from this species of Eucalyptus compared to messmate (Brice et al, 2019). Therefore it has been hypothesized that the inability of the majority of koalas to shift diets to messmate is due to a lack appropriate gut microbial assemblage for optimal digestion (Blyton et al, 2019). With the continuous threat of habitat loss and limited resources, the ability to shift diet and utilize different food sources is crucial for the survival and persistence of koalas in the wild.…”
Section: Gut Microbiome Management In Wildlife Conservationmentioning
confidence: 99%
“…Researchers recently showed that koalas were unable to switch between food tree species without the help of a faecal transplant pellet, containing a live microbiome sample from koalas that regularly ate the target tree species. Koalas that received the transplant established a gut microbiome more similar to koalas that ate the target species regularly, and were able to transition their diet to consume more of the target tree species (Blyton et al, 2019). This is one of the first studies to experimentally investigate the use of faecal transplants for conservation purposes-in this case, allowing dietary expansion in a highly specialized wild herbivore.…”
Section: Environmental Protection and Biodiversity Conservation Act 1995mentioning
confidence: 99%
“…Furthermore, koalas in these habitats exhibit high site fidelity and appear reluctant to move to alternate habitat types even when trees become completely defoliated (Whisson et al, ). Recent research into the koala's microbiome suggests that this may be due to koalas becoming highly specialized on a single food tree such that they may have limited ability to switch their diet to another food tree species (Blyton et al, ; Brice et al, ).…”
Section: Causes Of Overabundancementioning
confidence: 99%